Scientific understanding and representation : modeling in the physical sciences - Lawler, Insa; Khalifa, Kareem; Shech, Elay (New York, NY : Routledge, 2023)
"This volume assembles cutting-edge scholarship on scientific understanding, scientific representation, and their delicate interplay. Featuring several articles in an engaging 'critical conversation' format, the volume integrates discussions about understanding and representation with perennial issues in the philosophy of science, including the nature of scientific knowledge, idealizations, scientific realism, scientific inference, and scientific progress. In the philosophy of science, questions of scientific understanding and scientific representation have only recently been put in dialogue with each other. The chapters advance these discussions from a variety of fresh perspectives. They range from case studies in physics, chemistry, and neuroscience to the representational challenges of machine learning models; from special forms of representation such as maps and topological models to the relation between understanding and explanation; and from the role of idealized representations to the role of representation and understanding in scientific progress. Scientific Understanding and Representation will appeal to scholars and advanced students working in philosophy of science, philosophy of physics, philosophy of mathematics, and epistemology"--
Can scientific understanding be reduced to knowledge? / Henk W. de Regt -- Should friends and frenemies of understanding be friends? Discussing de Regt / Kareem Khalifa -- Frenemies or friends? A reply to Kareem Khalifa / Henk W. de Regt.
Keywords: Science -- Philosophy; Physics -- Philosophy; Physics -- Simulation methods; SCIENCE / Philosophy & Social Aspects; PHILOSOPHY / Epistemology